Increase in cardiac myosin binding protein-C plasma levels is a sensitive and cardiac-specific biomarker of myocardial infarction - Govindan, Suresh (e-Century Publishing Corporation, 2013)
Earlier studies have shown that cardiac myosin binding protein-C (cMyBP-C) is easily releasable into the circulation following myocardial infarction (MI) in animal models and patients. However, since its release kinetics has not been clearly demonstrated, no parameters are available to judge its efficacy as a bona fide biomarker of MI in patients with MI. To make this assessment, plasma levels of cMyBP-C and six known biomarkers of MI were determined by sandwich enzyme-linked immunosorbent assay in patients with MI who had before and after Percutaneous Transcoronary Angioplasty (PTCA), as well as healthy controls. Compared to healthy controls (22.3 ± 2.4 ng/mL (n=54)), plasma levels of cMyBP-C were significantly increased in patients with MI (105.1 ± 8.8 ng/mL (n=65), P<0.001). Out of 65 patients, 24 had very high levels of plasma cMyBP-C (116.5 ± 13.3 ng/mL), indicating high probability of MI. Importantly, cMyBP-C levels were significantly decreased in patients (n=40) at 12 hours post-PTCA (41.2 ± 9.3 ng/mL, P<0.001), compared to the patients with MI. Receiver operating characteristic analysis revealed that a plasma cMyBP-C reading of 68.1 ng/mL provided a sensitivity of 66.2% and a specificity of 100%. Also, myoglobin, carbonic anhydrase and creatine kinase-MB levels were significantly increased in MI patients who also had higher cMyBP-C levels. In contrast, levels of cardiac troponin I, glycogen phosphorylase and heart-type fatty acid binding protein were not significantly changed in the samples, indicating the importance of evaluating the differences in release kinetics of these biomarkers in the context of accurate diagnosis. Our findings suggest that circulating cMyBP-C is a sensitive and cardiac-specific biomarker with potential utility for the accurate diagnosis of MI.